2016
DOI: 10.1097/olq.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Sexually Transmitted Disease Screening in Clinic-Based Settings

Abstract: Successful interventions include changing clinic flow to routinely collect specimens for testing, using EHR screening reminders, and reminding patients to get screened or rescreened. These strategies can be tailored to different clinic settings to improve screening at a low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 60 publications
(152 reference statements)
2
42
0
Order By: Relevance
“…The strategy of providing continuing education credit has been demonstrated to improve human papillomavirus vaccination coverage in our network as well, and should be considered in future QI interventons. 30 Our results are consistent with a moderate intervention effect per the criteria identified by Taylor et al in their metaanalysis of STI screening interventions, 21 and are similar to the effect sizes identified in other recent screening interventions in the pediatric and adolescent clinical setting. We identified challenges in implementation largely related to role definition and work flow.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The strategy of providing continuing education credit has been demonstrated to improve human papillomavirus vaccination coverage in our network as well, and should be considered in future QI interventons. 30 Our results are consistent with a moderate intervention effect per the criteria identified by Taylor et al in their metaanalysis of STI screening interventions, 21 and are similar to the effect sizes identified in other recent screening interventions in the pediatric and adolescent clinical setting. We identified challenges in implementation largely related to role definition and work flow.…”
Section: Discussionsupporting
confidence: 89%
“…In a meta-analyses by Taylor et al, automatic collection of urine specimens as part of routine visits was identified as a moderately to highly effective and low-cost intervention to improve STI screening rates. 21 Our data reaffirm this finding, and provide additional support on how to implement this change in routine pediatric care. Other strengths of our intervention, and likely contributors to a higher than anticipated level of success, included the involvement and engagement of all levels of multidisciplinary clinical staff, the use of process mapping to identify site-specific barriers to facilitators of screening before intervention development, and the use of practice feedback to motivate ongoing behavior change.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…these are typically found to be effective as de ned as signi cant increases in the proportion tested or the frequency of testing (23,24). Indeed, in the ESSAHM Trial, we observed a three-fold increase in the odds of having at a least one syphilis test per year, and a doubling in the number of tests per year (25).…”
Section: Discussionmentioning
confidence: 83%
“…A recent study found that cost-effective interventions can be successfully designed to routinely collect specimen for STD testing by changing patient flow in clinical setting, using screening reminders through electronic health record systems, and training staff for frequent reminders to patients via text, e-mail, or postcard to encourage screening or re-screening for STDs. 21 …”
mentioning
confidence: 99%